Information Needs and Information-Seeking Behaviour of Students of Federal College of Dental Technology and Therapy (FCDT & T) Enugu, Nigeria - Oguonu, Oluchukwu C. (POMLIF Journal of Library and Information Science, 2019)
The study examine the information needs and information-seeking behavior among the students of the Federal College of Dental Technology and Therapy, Enugu, Nigeria. A total sample population of Two Hundred (200) respondents was selected from the four existing departments in the 2017/2018 academic session. The questionnaire was used as the research instrument for data collection. Simple percentages, tables, and frequencies were used for data analysis and presentation for easy interpretation. The findings indicate that the main information needs of students pertain to tasks involving academic research (190:97.44%) and information on tests and examinations (185: 94.89%), consultation with lecturers and collegues in the field (191:97.95%) and browsing through the internet (189:96.92%) are methods of seeking information for academic research. Conversely, the use of card catalogue (190:97.44%) is the tool for seeking information. The finding reveal that the college library (191:97.95%), personal collections (189:96.92%) and electronic database (187:95.90%) are most consulted and preferred source of information. The main barriers to information-seeking by students are the lack of reading and inadequate information materials (191:97.95%) which negatively correlates to the perception of success in meeting their information needs. In general students appear to be well satisfied with the selection of information sources and collection in meeting their needs. Hence, the study recommends the adequate provision of resources and the organizing of library user education at the beginning of every semester for all students to enhance their information seeking, and usage, in this dynamic information technology-driven era.